Corporate Governance Issues and Control in Conditions of Unstable Capital Risk - Lebedeva, Tatiana E.; Akhmetshin, Elvir M.; Dzagoyeva, Marina R.; Kobersy, Iskandar S.; Ikoev, Soslan K. (International Journal of Economics and Financial Issues, 2016)
In the context of deep and wide-ranging transformation of the Russian economy caused by a scientific and technological progress and its systemic and structural reforms undertaken in the process of forming a market economy and political democracy, before the Russian economic science alone raises issues of improving the control system. The main role plays a corporate governance practice, as it is large corporations is defined as the appearance of the national economy into the world economy and the main directions of its development, as well as the efficiency and competitiveness in the domestic and foreign markets. The problem of corporate governance research at the present time is one of the most important trends of modern economic research. Corporations in Russia still cannot cope with the role of a key link in our economy. In industrialized countries, it is an inherent part of the system of power (Osipov et al. 2016). At present, the largest business group management system is constantly refined. Develop vertically integrated holding companies, the combined unified scheduling, financing, coordination and supervision. The issues related to the optimization of corporate governance in the industrial holding company, while ensuring a reasonable level of autonomy of subsidiaries. Keywords: unstable markets, demand structure, influencing factors, business model JEL Classifications: G30, M21, D49